Isolation and Characterization of Chemical Compounds from Terminalia Chebula for Anti-Diabetic Evaluation Through In-Silico Approach : Pharmaceutical sciences- Pharmaceutics - Shikha; Thapa, Rahul; Arya, Girish Chandra; Arora, Saahil (International Journal of Life Science and Pharma Research, 2023)
Diabetes is a chronic metabolic disorder affecting millions of people and needs to be addressed. Alternativestrategies are required for better diabetes management, as evidenced by the high costs of modern medicines. The field of herbalmedicine research has been gaining significant importance in the last few decades, and the demand to use natural products in thetreatment of diabetes is increasing across the globe. Traditional plant medicines are used worldwide for a range of diabeticcomplications. Terminalia chebula is one of the widely used traditional medicine by diabetic patients. In this present work,Terminalia chebula fruits were used for the potential of anti-diabetic activity. The phytochemical investigation revealed that itsfruit contains high amounts of tannins, alkaloids, flavonoids, terpenoids, and glycosides. The percolation method was followed byusing T. chebula fruit for the extraction, further fractionating with different solvents, n-Hexane, Ethyl acetate, n- Butanol, andwater. When ethyl acetate extract of T. chebula was tested, it was found to have significant effects on blood glucose levels. Itsuggests that it can be used as an antidiabetic agent. Gallic acid and quercetin were compounds identified by NMR, MS, andUPLC analysis. Molecular docking studies of designed compounds were carried out through Auto Dock Vina [1.1.2] toinvestigate the interaction with PPAR-γ associated with diabetes, and pkCSM software was used for ADMET analysis. Thus, theresult of the study proved that the ethyl acetate extract of T. chebula had good potential as an antidiabetic, and this plant can beused to discover natural bioactive compounds that may serve for the advances of novel pharmaceutical development. Moreover,the compounds found in the extract could be used to develop new pharmaceuticals for diabetes treatment.